An Economic Analysis of Factors Influence on Profitability in Poultry Farming in Karnataka - Harsha B.D. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Poultry farming has become one of the fastest-growing agricultural sectors in India, significantly contributing to rural livelihoods, employment, and the availability of animal protein. In Karnataka, it plays a vital role in the rural economy, providing income and nutrition to small and medium-scale farmers. This study investigates the impact of selected economic and management factors on profit per bird among 60 poultry farms in Mysore District using an empirical farm-level approach. The study concludes that economic efficiency, feed management, and bio-security are the major drivers of profitability in poultry farming, while structural and minor cost factors play a limited role, providing actionable insights for farmers and policymakers.